Rate-based modelling of combined SO2 removal and NH3 recycling integrated with an aqueous NH3-based CO2 capture process - Li, K.; Yu, H.; Qi, G.; Feron, P.; Tade, Moses; Yu, J.; Wang, S. (Elsevier Ltd, 2015)
To reduce the costs of controlling emissions from coal-fired power stations, we propose an advanced and effective process of combined SO2 removal and NH3 recycling, which can be integrated with the aqueous NH3-based CO2 capture process to simultaneously achieve SO2 and CO2 removal, NH3 recycling and flue gas cooling in one process. A rigorous, rate-based model for an NH3–CO2–SO2–H2O system was developed and used to simulate the proposed process. The model was thermodynamically and kinetically validated by experimental results from the open literature and pilot-plant trials, respectively. Under typical flue gas conditions, the proposed process has SO2 removal and NH3 reuse efficiencies of >99.9%. The process is strongly adaptable to different scenarios such as high SO2 levels in flue gas, high NH3 levels from the CO2 absorber and high flue gas temperatures, and has a low energy requirement. Because the process simplifies flue gas desulphurisation and resolves the problems of NH3 loss and SO2 removal, it could significantly reduce the cost of CO2 and SO2 capture by aqueous NH3.